Optimization of Tourism Industry by Supply chain strategy of Rokan Regional District to Increase Original Revenue - Kasman Arifin ZA; Syapsan Syapsan; Dewi Puspa Suri (International Journal of Supply Chain Management, 2020)
Abstract- The paper aims to investigate the possible relationship between Tourism Supply Chain and Strategic Partnership, read as a way to reduce and better manage the complexity in Tourism Industry. Tourism in Indonesia in general and Rokan Hilir in particular have not been explored in totality. The true potential of Tourism to produce very large PAD and economic growth for the welfare of the community is very possible, given the potential of natural beauty and its people who are welcome to migrants. In fact, tourism activities in Rohil are still carried out sporadically, not well organized, so they don't know which events can produce and the name of the event is a people's party. To determine events or tourism destinations that have an impact on the economy of the community that can generate income from creative economic activities, a comprehensive study is needed. Optimization of Tourism Potential in Rokan Hilir aims to choose one of the many destinations and events in Rokan Hilir Regency which has the potential to be able to bring Foreign Tourists to Rokan Hilir Regency. The research method conducted here is a quantitative method using the Lean Six Sigma approach in analyzing and applying it. The results to be achieved from this study are 1) Rokan Hilir Regency's Leading Tourism Master Plan, 2) Impact Analysis of Rokan Hilir's Leading Tourism Determination